Studi Pemanfaatan Air Hujan Sebagai Sumber Air Baku Untuk Air Bersih Pada Kampus Universitas Bosowa Makassar - Maulina, Anandha; Yusuf, Andi Rumpang; Badrun, Burhanuddin (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
een changed to new buildings and settlements, resulting in a decrease in water catchment areas. Rainwater that cannot seep directly into the soil will result in inundation. If the inundation is not overcome, it will trigger flooding, so a rain catchment area is needed. This research is a study that presents field survey data aimed at planning water catchment buildings and clean water treatment plants at the Bosowa University Campus in Makassar. The area of rainwater catchment is 0.4477 ha and the rainfall intensity is 39.613, hence the rainwater discharge of 0.0469 m3 / second. From the results of data analysis, a rainwater harvesting system can be planned to be accommodated using a reservoir. The reservoir is planned from the results of data analysis of clean water needs at the Bosowa University Campus.